Makna Polisemi dalam Materi Bahasa Indonesia SD dan Implikasinya terhadap Pemahaman Siswa - Okta Vitriani; Aninditya Sri Nugraheni (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Polysemy is an important semantic phenomenon in Indonesian language learning in elementary schools because one word form can have more than one interrelated meaning. Understanding polysemy affects students' reading skills, text comprehension, and literacy development. However, studies that specifically examine polysemy in elementary school Indonesian language materials are still limited. This study aims to examine the forms of polysemy, how they are presented in Indonesian language textbooks for elementary schools, and their implications for student understanding. The study uses a qualitative approach with a literature review design. Data were obtained from semantics books and national and international journal articles published between 2017 and 2024 that were relevant to the research topic. Data analysis was conducted using content analysis techniques. The results of the study show that polysemy in elementary school Indonesian language materials appears in the form of context-based, functional, and extended meanings, with a presentation that is not yet fully systematic, thus potentially causing misconceptions and affecting students' reading comprehension.